Board gender diversity and sustainability reporting quality. Issue 3 (December 2016) - Al-Shaer, Habiba; Zaman, Mahbub
Abstract: Based on the notion that a diverse board will take a more balanced view and pay greater attention to social responsibility and stakeholder concerns, this paper examines the effect of board gender diversity, measured using a range of proxies, on sustainability reporting quality. After controlling for corporate governance as well as firm reporting incentives, reporting behaviour and reporting environment, we find that gender diverse boards are associated with higher quality sustainability reports and independent female directors have greater effect on sustainability reporting quality than female directors. Our findings have implications for policy formulation and provide evidence for a softer 'comply or explain' (as opposed to quota based) approach to encourage board gender diversity and its effects on sustainability reporting quality.